2022
DOI: 10.1038/s41421-022-00497-w
|View full text |Cite
|
Sign up to set email alerts
|

A bispecific nanobody dimer broadly neutralizes SARS-CoV-1 & 2 variants of concern and offers substantial protection against Omicron via low-dose intranasal administration

Abstract: Current SARS-CoV-2 Omicron subvariants impose a heavy burden on global health systems by evading immunity from most developed neutralizing antibodies and vaccines. Here, we identified a nanobody (aSA3) that strongly cross-reacts with the receptor binding domain (RBD) of both SARS-CoV-1 and wild-type (WT) SARS-CoV-2. The dimeric construct of aSA3 (aSA3-Fc) tightly binds and potently neutralizes both SARS-CoV-1 and WT SARS-CoV-2. Based on X-ray crystallography, we engineered a bispecific nanobody dimer (2-3-Fc) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…Importantly, both C-282 and C-39 showed superior affinities when binding to multiple SARS-CoV-2 variants compared to previously reported nanobodies (Figure ). , Furthermore, a comparison with results from pseudovirus experiments revealed that these nanobodies exhibit high neutralizing activity against multiple mutant variants, with IC 50 values comparable to those of previously reported nanobodies (Supporting Information Table S2).…”
Section: Resultssupporting
confidence: 73%
“…Importantly, both C-282 and C-39 showed superior affinities when binding to multiple SARS-CoV-2 variants compared to previously reported nanobodies (Figure ). , Furthermore, a comparison with results from pseudovirus experiments revealed that these nanobodies exhibit high neutralizing activity against multiple mutant variants, with IC 50 values comparable to those of previously reported nanobodies (Supporting Information Table S2).…”
Section: Resultssupporting
confidence: 73%
“…So far, several Nbs have been developed with promising diagnostic and therapeutic applications [20,38]. Both monomeric Nbs and engineered molecules showed strong neutralizing activity to the different VOCs that have emerged, including the Omicron variants [39][40][41][42][43][44][45][46]. The intense production of new recombinant Nbs highlights the relevance of this technological platform, which is expected to reach clinical use for SARS-CoV-2 and other viral diseases in the near future [47].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, nanobodies consist of only one Ig domain and are thus easier to engineer in a multivalent format than conventional antibodies. A specific nanobody dimer has been reported to exhibit robust improved neutralization potency and broad-spectrum activity against both SARS-CoV-1 and SARS-CoV-2 strains [17]. However, there are few reports on the avidity of multivalent nanobodies and the development of diagnostic assays using multivalent genetic engineering [18,19].…”
Section: Introductionmentioning
confidence: 99%